PENGARUH KEPRIBADIAN TERHADAP KINERJA PEGAWAI DIMEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada Pegawai Biro Umum Sekretariat Daerah Provinsi Nusa Tenggara Timur) - Ridolof W. Batilmurik; Emanuel Yansen Faymau (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to analyze the mediating role of Organizational Citizenship Behavior (OCB) and the relationship between personality and employee performance. The research was conducted by taking 53 members of the population as research samples from all employees of the General Bureau of the Regional Secretariat of East Nusa Tenggara Province with an explanatory quantitative approach. The analytical tool used is a path analysis based on the Structural Equation Modeling (SEM) with the help of SmartPLS version 3.3. The results showed that: 1) Personality had a positive but not significant effect on employee performance; 2) Personality has a positive and significant effect on OCB; 3) OCB has a positive and significant effect on employee performance and; 4) OCB mediates the relationship between personality and employee performance.